From confinement to deconfinement of magnetic monopoles in artificial rectangular spin ices - F S Nascimento; L A S Mól; W A Moura-Melo; A R Pereira (New Journal of Physics, 2012)
We study a frustrated two-dimensional array of dipoles forming an artificial rectangular spin ice with horizontal and vertical lattice parameters given by a and b respectively. We show that the ice regime could be stabilized by appropriate choices for the ratio γ ≡ a / b . Our results show that for $γ ≈ \sqrt {3}$ , i.e. when the centers of the islands form a triangular lattice, the ground state becomes degenerate. Therefore, while the magnetic charges (monopoles) are excitations connected by an energetic string for general rectangular lattices (including the particular case of a square lattice), they are practically free to move for a special rectangular lattice with $γ ≈ \sqrt {3}$ . Besides that, our results show that for $γ > \sqrt {3}$ the system is highly anisotropic in such a way that, even for this range out of the ice regime, the string tension almost vanishes along a particular direction of the array. We also discuss the ground state transition and some thermodynamic properties of the system.